First Records of an Estuarine Goby Acentrogobius ocyurus (Gobiiformes: Gobiidae) from Japan and the Sulu Sea in the Philippines - Kunishima, Taiga; Palla, Herminie P.; Tachihara, Katsunori; Maeda, Ken (Species Diversity, 2022)
Twenty specimens of Acentrogobius ocyurus (Jordan and Seale, 1907) were collected in Manko, Okinawa-jima Island, Japan and Sulu Sea side of Puerto Princesa City, Palawan Island, Philippines. As the species had previously been reported from the South China Sea, Andaman Sea, and northern Australian waters, these specimens from Okinawa and Palawan represent the first records of the species from Japan and the Sulu Sea. Acentrogobius ocyurus was found on muddy substrata at the lowest tidal zone of the mudflat and was often found in burrows of mangrove pistol shrimp, Alpheus richardsoni Yaldwyn, 1971. Morphological traits suggested that A. ocyurus is closely related to A. globiceps (Hora, 1923), A. kranjiensis (Herre, 1940), and Acentrogobius sp. (“Suzume-haze” in Japanese name), with several homologous features including, the transverse pattern of the sensory papillae on the cheek, caudal fin pointed in middle, a black stripe behind the eye along the anterior oculoscapular canal, bright blue spots laterally on the body, and an oblique yellow stripe across the upper part of the caudal fin.